Dairy Cows Transition Period Feeding and Management - Mushfiq, Sayed Rahimullah; Aabidy, Mohammad Hassan; Rafed , Rizwanullah (Journal for Research in Applied Sciences and Biotechnology, 2023)
Proper feeding during the pregnancy and post-pregnancy period, determines the milk Production, ensuing lactation and as well as, the reproductive efficiency of the animal. 3 weeks before and 3 weeks after parturition are very important because a dramatic physiological and metabolic adaptation occurs during this period which is called the transition period. The Nutritional imbalances are caused by the low quality of desired nutritious rations, reduced appetite, and low ingestion which are responsible for depressed performance, specifically during the transition period. The absence of knowledge and skills of farmers in feeding management during the transition period exacerbates the situation. The metabolic changes, metabolic adaptations, Mechanism of a Transition period, transition period feeding management to prevent disorder, Decreased dry matter intake (DMI), Nutrient requirements, Infectious diseases and metabolic disorders, Nutritional management to Ease out the Transition Period, Management of the transition period, Feed additives supplementation and nutritional-management strategies to passage transition period are discussed by this review paper. Simultaneously, with the growth of the fetus, the nutrient requirements increase and are at their peak before parturition as well as immediately after parturition. The peak milk production reaches about 5–8 weeks postpartum, while the diet consumption peaks at 10–14 weeks postpartum. So, dairy cows will typically suffer a 6–8-week period of negative energy balance during the postpartum period. The requirement energy of the mammary at 4 days postpartum is more than three times than that of the uterus, with a simultaneous increase in the requirement of metabolizable protein, especially of methionine and lysine. The high metabolic incidence of infectious diseases is responsible for the high incidence of inflammatory conditions, mostly immediately after calving. To prevent mentioned diseases, pro-inflammatory cytokine release should be avoided postpartum. The body reserves mobilization, especially fat and protein; and hepatic gluconeogenesis takes place immediately after parturition leading to increased levels of β-hydroxy butyric acid and non-esterified fatty acids, which act as a gateway for several metabolic diseases. The phase of transition may eased by increasing DMI, feed conversion efficiency, density of ration, and protein supplements rich in rumen un-degradable protein; by using anionic mineral mixture, optimizing roughage to concentrate (R: C) ratio, optimum physically effective fiber length of forages/silage/hay, dietary buffers, feed additives such as inflammation modulators, protected nutrients, glucogenic precursors and direct-fed microbial/probiotics.